Assessment of lung cancer risk factors and mortality in Qatar: A case series study. Issue 1 (7th October 2020) - Abdel‐Salam, Abdel‐Salam G.; Mollazehi, Mohammad; Bandyopadhyay, Dipankar; Malki, Ahmed M.; Shi, Zumin; Zayed, Hatem
Abstract: Background: The global burden of cancer has exponentially increased over the last few years. In 2018 alone, approximately more than half of the 18.1 million individuals who had cancer succumbed to it. Lung cancer cases and fatalities are particularly on the rise. Therefore, exploring the factors surrounding lung cancer mortality is of utmost importance. Aims: We investigate the clinicopathological and epidemiological characteristics of patients with lung cancer undergoing treatments, and their 5‐year survival rates from a case series study in Qatar. Methods and Results: All patients' data (between January 2010 and December 2014) in this case series study were retrieved from Al‐Amal Hospital database. Kaplan‐Meier survival plots, life tables and Cox regression were utilized for the statistical analysis. A total of 229 lung cancer patients were included in this study; of which 23.6% are Qatari (40 males and 14 females) and 76.4% non‐Qatari (133 males and 42 females). Approximately 57.6% of our patients received at least one type of treatment. We observe a 5‐year survival rate of 9.4% in our patient cohort. We also observe other predictive factors, such as distant metastasis (adjusted hazards ratio, HR = 2.414, 95% CI: 1.035‐5.632), smoking status (adjusted HR = 3.909, 95% CI: 1.664‐9.180) and the treatment history (adjusted HR = 0.432, 95% CI: 0.270‐0.691), to be significant. Conclusion: Lung cancer is a prevalent health condition in Qatar, particularly owing to the rising use of tobacco in the country. The survival rate for lung cancer patients in this country is lower, compared to the global average. Moreover, several factors such as distant metastasis, smoking status, and treatment history are associated with lung cancer survival in Qatar.